Delayed response of microbial epipelic biofilm to nutrient addition in a Pampean stream - Cochero, Joaquin (2013)
In streams and rivers, the first organisms which directly receive and respond to nutrients are primary producers (algae, macrophytes) and microbial heterotrophs (bacteria, fungi) since they rely on available inorganic nutrients from the water column. The aim of the present study was to analyze the response of the epipelic microbial biofilm in a Pampean stream submitted to a continuous input of inorganic nutrients (nitrogen and phosphorus). For this purpose, we measured the effects of moderate nutrient addition during 14 mo on the epipelic biofilm community of a meso-eutrophic stream that runs through the Pampean plain. The effects of nutrient enrichment were tested by analyzing the difference in algal and bacterial biomass and 2 extracellular enzymatic activities (β-glucosidase, phosphatase) at an enriched reach compared with those measured at an unmodified upstream reach. Overall, the response of the epipelon of this Pampean stream produced a slow and delayed effect on algal biomass increases, which might result in a delayed effect on the increase of bacterial densities. Neither phosphatase activity nor β-glucosidase activity exhibited significant changes due to nutrient addition. This may be due to the fact that the phosphatase activities measured were basal activities, uninhibited by enrichment, and that the epipelic β-glucosidase activity was regulated more by substrate availability than by any nutrient imbalance. Although changes are slow, if some of these changes were to become chronic, they would affect the functioning and services of the whole stream ecosystem.